Pemphigus Vulgaris: Pentingnya Diagnosis Dini, Penatalaksanaan yang Komprehensif dan Adekuat (Laporan Kasus) - Sri Rezeki; Titiek Setyawati (Faculty of Dentistry, Universitas Indonesia, 2012)
Pemphigus vulgaris is an autoimmune-mediated disease of skin and mucous membran leading to progressive blistering and chronic erosions. It often begins with blister formations which easily rupture. The characteristic feature is positive nikolsky sign which may or not be presented simultaneously. Establishment of early definite diagnosis is critical and requires correlation of clinical and histopathological findings. Because of this conditon is a potentially life-threatening, the risk of complications and mortality rate increases if initial management is non comprehensive and inadequate. Treatment is directed at supression of autoimmune process, typically administration of corticosteroids. This article report a case in a 51 years old woman who had painful chronic oral ulcer and poor general health condition. Prior to the visit to Oral Medicine clinic, patient was treated by her general practitioners for several months, without either established diagnosis nor comprehensive and adequate management, so that she had no clinical improvement. Clinical examination at the first visit in Oral Medicine clinic Cipto Mangunkusumo Hospital, revealed bula in the skin, conjunctivitis, easily bleed oral mucosae, widespread erosions and ulcerations of the lips, gingiva, tongue, and buccal mucosae. Biopsy of one of skin erosions demonstarting suprabasal intraepithelial acantholysis. Multi divisions in Hospital, such as Oral Medicine, Dermatology, Internal Medicine, Ophtalmology, ENT, were involved in treating this case. Patient received high dose methylprednisolone sistemically and prednisone topically for the lips. General remission achieved in several days. Thus, establishment of early definite diagnosis and adequate management are important in management of Pemphigus vulgaris. DOI: 10.14693/jdi.v16i1.20